Determination of Copper and Study Its Poisonous Effects in Drinking Water in Baghdad area - Khalid N. Jassim (College of Pharmacy / Mustansiriyah University, 2013)
The objective of this study is to determine the concentration of copper(mg/L) in drinking water by using chromogenic agent from different area in Baghdad & with different intervals , The results show that the concentration of copper ( mgŁ) in tap water which remains motionless in plumbing system for following periods one hours, 3 hours, 6 hours, 12 hours, 24 hours, 7 days and 14 days are 1, 2.2, 4, 5.3, 7.5, 10 and 16 mgŁ respectively. From these results it clear that a high levels of copper occur if corrosive water comes in contact with copper plumbing and copper-containing fixtures in the water distribution system. If corrosive water remains motionless in the plumbing system for some time. These amounts of copper are believed to have given rise to the symptoms of chemical food poisoning precipitated by the ingestion of alcohol on an empty stomach. Also children under one year of age are more sensitive to copper than adults. Long-term exposure (more than 14 days) to copper in drinking water which is much higher than 1,000 ug/I has been found to cause kidney and liver damage in infants.